Disease-resistant feed for fragrance pigs - FANG BAOFENG (2018)
The invention discloses a disease-resistant feed for fragrance pigs. The disease-resistant feed comprises alfalfa, broken peanuts, soybean peel, Chinese yam powder, dandelions, earthworms, rhizoma coptidis powder, centella asiatica, chingma abutilon seeds, pinellia tubers and garlic powder. The disease-resistant feed can effectively promote growth of fragrance pigs and reduce the attack rate of the fragrance pigs. 本发明公开了种抗病香猪饲料，包括苜蓿草、花生碎、大豆壳、山药粉、蒲公英、地龙、黄连粉、积雪草、冬葵子、半夏和大蒜粉。本发明能够有效的促进香猪的生长,减少香猪得病率。